LAW ENFORCEMENT CHALLENGES IN TRAFFIC FOR STUDENTS: BETWEEN REALITY AND IDEALISM - TENRI FAMAURI, ANDI; RIFAI, AULIA; UTAMI MAS BAKAR, DIAN; WENDA JUNIAR, MUTIAH; TH. HOESA, FADHLURRAHMAN; JALU PRASETYO, ADJI (Sekolah Tinggi Ilmu Hukum Awang Long, 2020)
Students are one of the vulnerable groups who become the victim or perpetrators of traffic accidents. Adolescents in 17-21 years old are categorised as the biggest number of students who become perpetrators. It happens due to the basic driving skill level, the less experience in driving and unstable emotions. The young drivers tend not to own the ability to perceive a risky condition which closely related to the immaturity of driving experience and the will to take risky decisions. This research found that one of the ideal forms of fostering students who are among the highest contributors to the accident and violations of traffic is through legal counselling activities which increase their legal awareness. This is in line with the provision in Article 4 of Law Number 22 Year 2009 concerning Traffic and Land Transportation which stipulate that to foster and implement safe, secure, orderly and smooth traffic and transportation, one of the ways is through traffic education. In increasing the legal awareness of traffic on students through legal counselling methods, at least students are given the knowledge and understanding of proper traffic procedures and criminal sanctions that can be imposed if committing a traffic violation.